Thematic structures in conference papers by Persian EFL scholars - Naderi, Sahar; Koohestanian, Farhang (Elsevier, 2014)
Thematic structure, positioning and organization of messages in the clauses are important features in a textual investigation of any discourse. In higher education, thematic structures play a crucial role in making any written discourse successful and progressive. This study investigates thematic structures in conference papers of Persian postgraduate students in the engineering fields via Hallidayan Systemic Functional Grammar (Halliday, 1994; Halliday & Matthiessen, 2004). In addition, meaningful differences in the thematic organizations of the two sections of the papers (Methodology and Results and Discussion) are revealed.